2018
DOI: 10.1007/s10714-018-2346-8
|View full text |Cite
|
Sign up to set email alerts
|

The tunneling radiation of a black hole with a f(R) global monopole under generalized uncertainty principle

Abstract: We consider the evolution of black hole involving an f (R) global monopole based on the Extended Uncertainty Principle (EUP). The black hole evolutions refer to the instability due to the Parikh-Kraus-Wilczeck tunneling radiation or fragmentation. It is found that the EUP corrections make the entropy difference larger to encourage the black hole to radiate more greatly. We also show that the appearance of the EUP effects result in the black hole's division. The influence from global monopole and the revision o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 94 publications
(252 reference statements)
0
5
0
Order By: Relevance
“…As mentioned above that the generalizations of the principle undoubtedly modify the horizons and further the entropy, the GUP has influence over the tunneling radiation and fragmentation of black holes [28,[34][35][36][39][40][41][42]. In the context of the GUP modifying quantum mechanics [27][28][29][30][31][32][33][34][70][71][72][73][74][75], the authors of Refs. [35,36] derived and estimated the relation between the Hawking tunneling radiation of black holes and a minimal length as the quantum gravity scale in the higher dimensional spacetime by means of the tunneling formalism.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above that the generalizations of the principle undoubtedly modify the horizons and further the entropy, the GUP has influence over the tunneling radiation and fragmentation of black holes [28,[34][35][36][39][40][41][42]. In the context of the GUP modifying quantum mechanics [27][28][29][30][31][32][33][34][70][71][72][73][74][75], the authors of Refs. [35,36] derived and estimated the relation between the Hawking tunneling radiation of black holes and a minimal length as the quantum gravity scale in the higher dimensional spacetime by means of the tunneling formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to generate the effective acoustic metric, we incorporate the contribution of the minimum length with this prescription into the Lagrangian. In recent years, the exploration of models considering the GUP effect has been a subject of great interest in the literature [67][68][69][70][71][72][73][74][75][76][77]. In particular, the analysis of the effect of the GUP on Hawking radiation has been an issue that has been widely explored by many authors [78][79][80][81][82][83][84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%
“…For a review of GUP, see [47]. GUP is one of the simplest models of effective quantum gravity, and many interesting results in the study of black hole physics have been produced [48][49][50][51][52][53][54][55][56][57][58][59]. Specifically, the authors of [60] discussed the effect of quantum gravity on the weak cosmic censorship conjecture and showed that the second law of thermodynamics and the cosmic censorship conjecture are violated owing to the rainbow effect.…”
Section: Introductionmentioning
confidence: 99%